Complex regional pain syndrome in an adolescent with conservative treatment of a scaphoid distal pole fracture - Travis Jebackumar, MS; Claudio Silveri, MD; Sumit K. Gupta, MD, MPH; Ana C. Belzarena, MD, MPH, MBA (Radiology Case Reports)
Complex regional pain syndrome (CRPS) is a rare, chronic neuropathic pain disorder, particularly uncommon in adolescent populations and rarely associated with scaphoid fractures. We present the case of a 16-year-old female who developed CRPS following a minimally displaced scaphoid fracture treated conservatively with immobilization. The patient experienced persistent pain, hyperalgesia, trophic changes, and diffuse osteopenia, consistent with CRPS. Early diagnosis, where radiographs played a key role, and treatment with vitamin C and gabapentin led to the resolution of symptoms and recovery, emphasizing the critical importance of timely intervention. This case underscores the rarity of CRPS following scaphoid fractures in adolescents, highlights the need for increased clinical awareness, and further research to optimize outcomes in atypical presentations.